2008
DOI: 10.1007/s11340-008-9203-8
|View full text |Cite
|
Sign up to set email alerts
|

A Procedure for Accurate One-Dimensional Strain Measurement Using the Grid Method

Abstract: This paper deals with the accurate calculation of strain using the grid method. The strain field is first directly deduced from the fringe pattern without calculating the displacement field. This procedure is validated with two numerical examples. Two types of experiment are then carried out: a translation and a tensile test. It is observed that some additional fictitious strains appear in both cases. They are due to two main reasons which interact with each other: the grid defects and the displacement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 26 publications
1
52
0
Order By: Relevance
“…These quantities are directly proportional to the in-plane displacement and strain components, respectively [11]. It has been shown that the metrological performance of this technique could be significantly improved (especially for strain measurements) by getting rid of most of the grid marking defects which unavoidably occur when grids are printed on their support [12,13]. This leads to a good compromise between resolution and spatial resolution of the measurements.…”
Section: The Grid Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These quantities are directly proportional to the in-plane displacement and strain components, respectively [11]. It has been shown that the metrological performance of this technique could be significantly improved (especially for strain measurements) by getting rid of most of the grid marking defects which unavoidably occur when grids are printed on their support [12,13]. This leads to a good compromise between resolution and spatial resolution of the measurements.…”
Section: The Grid Methodsmentioning
confidence: 99%
“…Full details on small strain calculation can be found in Refs. [12,13] for unidirectional and crossed grids, respectively.…”
Section: The Grid Methodsmentioning
confidence: 99%
“…[14] proposed a new derivation procedure for grid techniques. The technique is twofold: first, it consists in deriving the wavelet used for the phase extraction.…”
Section: Basic Principlementioning
confidence: 99%
“…We noted here the following specific "phase culture" items: camera distortion can be evaluated with a single grid image [12], shape and shape variation can be detected in very good conditions using a video-projector and a camera [13]. Last, derivation can be derived analytically and the grid technique becomes sensitive to strain rather than displacements [14]. This item should bring to such method a breakthrough compared to DIC techniques; it will be developed in the following.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison between DIC and digital speckle pattern correlation to measure displacement fields in a Cu-AlBe SMA was presented in Reference [10]. The grid method [11] was used on a monocrystalline Cu-Al-Be [12], including a specific procedure to limit some negative effects of unavoidable grid defects [13,14]. This procedure limited the use of spatial filtering to reduce noise in strain maps, leading to a good compromise between strain resolution and spatial resolution in strain, and thus making possible the detection of very localized phenomena such as appearance and development of thin martensite needles.…”
Section: Introductionmentioning
confidence: 99%